Want this question answered?
Be notified when an answer is posted
g(x) = x/2
fx=5x1 / 9
3
15x2-13x+2 = (5x-1)(3x-2) when factored
7+3w-13x
g(x) = x/2
fx=5x1 / 9
3
(13x)2 = 169x2
-x^2 -13x -40 = -(x^2 + 13x + 40) = -(x + 5)*(x + 8)-x^2 -13x -40 = -(x^2 + 13x + 40) = -(x + 5)*(x + 8)-x^2 -13x -40 = -(x^2 + 13x + 40) = -(x + 5)*(x + 8)-x^2 -13x -40 = -(x^2 + 13x + 40) = -(x + 5)*(x + 8)
29
y=x
15x2-13x+2 = (5x-1)(3x-2) when factored
The GCF is 13x
7+3w-13x
5x^2 - 13x = x(5x - 13)
If you mean 4x-13x = 2, then-9x = 2-9x/-9 = 2/-9x = -2/9